AN ANALYSIS OF ULIL ABSHAR ABDALLA’S “ENVIRONMENTAL WAHHABI” CONCEPT IN THE CONTEXT OF MINING ISSUES ON SOCIAL MEDIA (A NORMAN FAIRCLOUGH PERSPECTIVE) - Yuliana Anggraeni A; Istnan Hidayatullah; Kamridah Kamridah; Surni Kadir (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study investigates how the phrase 'Environmental Wahhabi,' introduced by prominent Indonesian Muslim intellectual Ulil Abshar Abdalla, functions as a discursive mechanism to delegitimize environmental activism amid the nickel mining controversy in Raja Ampat. Drawing on Norman Fairclough's Critical Discourse Analysis (CDA) framework, the study examines a post published on the X (Twitter) platform on June 10, 2025, alongside Ulil's verbal statements during the ROSI KompasTV debate on June 12, 2025. Three interlocking analytical dimensions are applied: textual, discursive practice, and social practice. Findings reveal that at the textual level, the phrase operates through semantic borrowing from religious discourse, the application of layered delegitimization rhetoric, and a naturalizing analogy that reframes ecological debate as a matter of activist character rather than environmental substance. At the discursive practice level, the term spread virally across digital platforms but was predominantly met with public rejection. At the social practice level, the phrase structurally aligns with Indonesia's dominant developmentalist ideology, amplified by Ulil's considerable symbolic capital as a Nahdlatul Ulama intellectual. Ultimately, the study concludes that 'Environmental Wahhabi' functions as an instrument of discursive hegemony that normalizes mining acceptance as the rational and moderate position while stigmatizing its critics as fanatics.